AsCas12a ultra nuclease facilitates the rapid generation of therapeutic cell medicines - Liyang Zhang (Nature Portfolio, 2021)
The utility of AsCas12a can be limited to poor editing efficiency. Here the authors identify a variant, “AsCas12a Ultra”, that has high on-target specificity demonstrated through editing of clinically relevant T cell genes.